Quality for home palliative care: an Italian metropolitan multicentre JCI-certified model. Issue 1 (1st March 2012) - Rizzi, Franco; Pizzuto, Massimo; Lodetti, Laura; Corli, Oscar; Da Col, Daria; Damiani, Maria Eugenia; Mihali, Dorian; Piva, Laura; Saita, Luigi; Vinci, Maria; Bonaldi, Antonio
Abstract : Background: Assessing the quality of care and service delivery through the analysis of ad hoc indicators is a relevant process for quality monitoring and improvement with a view to providing patients, the community and administrators alike with appropriate elements of evaluation. This paper describes the key results of a certification process based on the Joint Commission International (JCI) criteria for the home hospitalisation model implemented by the palliative care units of seven Milan hospitals for terminally ill patients with cancer. Methods: In 2006, the interhospital working team implemented a certification project based on the JCI Disease or Condition-Specific Care (DSCS) programme. Thirty standards subdivided into five functional areas with 150 measurable elements were the starting-point for periodic improvement plans within and across participating hospitals. Programme compliance was analysed in terms of annual performance improvement and consistency across the seven PCUs involved in achieving set goals. The JCI standards were applied on 3316 terminally ill patients with cancer treated at home from 2005 to 2009. Results: As a result of the work carried out, the JCI survey conducted 3 years after project implementation demonstrated full compliance with the established standards, leading to the JCI certification award (for the first time in this clinical setting internationally). Conclusion: The work carried out with a view to certification has confirmed the possibility that facilities spread across different hospitals can actually share common processes and standardise the activities for the care of end-of-life patients with cancer at home as if they were one single service provider.